Genome-wide association study and functional characterization identifies candidate genes for insulin-stimulated glucose uptake: article - Williamson, Alice M.; Norris, Dougall M.; Yin, Xianyong; Broadaway, K. Alaine; Moxley, Anne H.; Vadlamudi, Swarooparani; Wilson, Emma P.; Jackson, Anne U.; Ahuja, Vasudha; Andersen, Mette K.; Arzumanyan, Zorayr; Bonnycastle, Lori L.; et al. (Nature genetics, 2023)
Distinct tissue-specific mechanisms mediate insulin action in fasting and postprandial states. Previous genetic studies have largely focused on insulin resistance in the fasting state, where hepatic insulin action dominates. Here we studied genetic variants influencing insulin levels measured 2 h after a glucose challenge in >55,000 participants from three ancestry groups. We identified ten new loci (P < 5 × 10−8) not previously associated with postchallenge insulin resistance, eight of which were shown to share their genetic architecture with type 2 diabetes in colocalization analyses. We investigated candidate genes at a subset of associated loci in cultured cells and identified nine candidate genes newly implicated in the expression or trafficking of GLUT4, the key glucose transporter in postprandial glucose uptake in muscle and fat. By focusing on postprandial insulin resistance, we highlighted the mechanisms of action at type 2 diabetes loci that are not adequately captured by studies of fasting glycemic traits.